2013
DOI: 10.1016/j.breast.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent treatment with gonadotropin-releasing hormone agonists for chemotherapy-induced ovarian damage in premenopausal women with breast cancer: A meta-analysis of randomized controlled trials

Abstract: Concurrent administration of GnRH agonists during chemotherapy treatment of breast cancer in premenopausal women appears to protect against chemotherapy-related POF in the first year after treatment, but appears to have no effect on resumed menses or spontaneous pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 32 publications
1
51
1
Order By: Relevance
“…[132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition. 135,136 Further, results from earlier meta-analyses were inconsistent, with some showing a potential benefit of GnRH to preservation of ovarian function, [137][138][139] while other reviews have been unable to come to this conclusion. 140,141 Also, limited data are available on the long-term impact of GnRH on preservation of ovarian function, 132 though a 5-year follow-up analysis of a randomized trial showed that administration of a GnRH agonist does not significantly impact premature ovarian failure or future pregnancy rate.…”
Section: Options For Femalesmentioning
confidence: 99%
“…[132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition. 135,136 Further, results from earlier meta-analyses were inconsistent, with some showing a potential benefit of GnRH to preservation of ovarian function, [137][138][139] while other reviews have been unable to come to this conclusion. 140,141 Also, limited data are available on the long-term impact of GnRH on preservation of ovarian function, 132 though a 5-year follow-up analysis of a randomized trial showed that administration of a GnRH agonist does not significantly impact premature ovarian failure or future pregnancy rate.…”
Section: Options For Femalesmentioning
confidence: 99%
“…Furthermore, sample size calculation was not conducted in some studies 24,27,28,32,33 and, when calculated, the required number of participants was not reached in others 23,25,26,29,31,35 . Previous systematic reviews with meta-analysis have addressed the effect of GnRHa on reproductive outcome of women with cancer undergoing chemotherapy, but their inclusion criteria differed from the present review as they included observational studies 12,15 or were restricted to breast cancer [17][18][19][20][54][55][56][57] . The conclusions of these previous reviews ranged from GnRHa having no significant impact on chemotherapy-induced amenorrhea 54 , to an association of GnRHa with lower risk of POI and higher pregnancy rate, suggesting that GnRHa 'might be considered as an option' for ovarian function preservation 57 .…”
Section: Lymphomamentioning
confidence: 99%
“…Gonadal protection through hormonal manipulation with GnRH analogs for FP in women treated with gonadotoxic chemotherapy has demonstrated conflicting results (3,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Published clinical guidelines from clinical associations are variable in their recommendations regarding GnRH analogs.…”
Section: Usefulness Of Gonadotropin-releasing Hormone (Gnrh)mentioning
confidence: 99%